2011
DOI: 10.1111/j.1600-0501.2011.02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transcrestal sinus floor elevation with graft biomaterials. A randomized clinical trial

Abstract: The Smart Lift technique in conjunction with the additional use of either S-HA or DBBM may provide a predictable elevation of the maxillary sinus floor along with limited post-surgical complications and post-operative pain/discomfort. SL and aGH were significantly greater at 6 months for S-HA than DBBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(104 citation statements)
references
References 32 publications
8
93
0
3
Order By: Relevance
“…The procedure investigated in this study was also performed in the implant sites with a ABH less than 3 mm, even if the initial implant stability was not optimum in all cases, so the minimum recommended ABH was 3 mm for this study. Most publications on vertical bone gain in sinus transcrestal elevation reported an average of less than 5 mm (19). The amount of bone gain reported with TGSL technique used in this study was 6.4 ± 1.6 millimeters and this gain was maintained for all 3 years of radiographic examinations.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The procedure investigated in this study was also performed in the implant sites with a ABH less than 3 mm, even if the initial implant stability was not optimum in all cases, so the minimum recommended ABH was 3 mm for this study. Most publications on vertical bone gain in sinus transcrestal elevation reported an average of less than 5 mm (19). The amount of bone gain reported with TGSL technique used in this study was 6.4 ± 1.6 millimeters and this gain was maintained for all 3 years of radiographic examinations.…”
Section: Discussionmentioning
confidence: 56%
“…Subsequently, various modifications to the original technique have been performed in order to improve the reliability and safety, such as: the introduction of the osteotome for the sinus lift (17), the osteotome for positioning of bone (37) and the use of a balloon catheter for the membrane lifting (38)(39)(40)(41). Fractures or perforation of the sinus floor are the main complications related to the transcrestal approach with technique of osteotomes (14,16,17) and drills with (18,19) or without (15) depth stop; the limitations of this surgical approach are represented by: impossibility of a direct visualization of the sinus cavity and of the Schneider membrane, limited amount of bone increase and high risk of accidental perforation of the membrane, without the possibility of surgical repair than the lateral approach. In patients with severely maxillary bone resorption is recommended a conventional approach with surgical lateral window because of perceived limitations with the transcrestal approach (42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,11,24,25] As regards the sinus floor elevation effect of AOT, it is clear that the amount of vertical bone gain was smaller than that reported in other studies, where transcrestal sinus floor elevation was achieved by means of osteotomes and burs plus autogenous bone and graft biomaterial (6.75 mm), [26] osteotomes plus deproteinized bovine bone mineral (DBBM) (6.9 mm) [27] or osteotomes and burs plus synthetic hydroxyapatite or DBBM (7.70 and 6.50 mm, respectively). [28] However, the majority of studies where sinus elevation was performed by means of the use of osteotomes alone or combinations of osteotomes and burs, with or without graft material, reported a mean vertical bone gain lower than 5 mm. [29À37] AOT makes it possible to minimize the risk of intraoperative and postoperative complications, creating an adequate implant site for the placement of a conventional-sized implant.…”
Section: Resultsmentioning
confidence: 99%
“…[25]. The smart lift technique research has demonstrated the biomaterial used in association with it, may provide a predictable elevation of the maxillary sinus floor along with limited post-surgical complications and postoperative pain/discomfort [26]. Thus, Smart Lift technique represents a minimally-invasive surgical option for sinus floor elevation aimed at preventing surgical complications [20].…”
Section: Transcrestal Approach (Tsfe)mentioning
confidence: 99%